DESIGN OF REACTOR AND CONDENSOR OF COCONUT SHELL LIQUID SMOKE CAPACITY 35O KG/PROCESS - Gafur, Abdul (Universitas Muhammadiyah Jakarta, 2021)
The problem faced by the coconut shell charcoal business group is that a lot of smoke is produced from the combustion process. The process of processing coconut shells into charcoal still uses the manual method, which is burned using used drums so that the smoke from the combustion process is very disturbing to the surrounding environment. Another problem is the capacity of used drums is very limited, one process can only process 100 kilograms of coconut shells, if the production is 1 ton per day it will take 10 pieces of used drums, this results in inefficient work and requires extra energy. Another problem that is also very disturbing is smoke pollution resulting from burning coconut shells. This smoke pollution is very disturbing to the surrounding environment so it needs special handling to remove this smoke. The entrepreneurs do not yet have the knowledge of technology that can be used to reduce smoke pollution and make processing work more efficient. Therefore, in this study, a research will be conducted on the efficiency of the coconut shell liquid smoke condenser. In this research, 1 reactor and condenser will be designed and built with a capacity of 500 kg coconut shell for each process, the technology used is gasification system and liquid smoke technology uses condenser technology and spiral pipe as smoke condenser. The research method that will be carried out will use the method of design, calculation and the process of making tools.